2012 IEEE 75th Vehicular Technology Conference (VTC Spring) 2012
DOI: 10.1109/vetecs.2012.6240057
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Power Allocation for a Two-Path Successive Relay System with Full Interference Cancellation

Abstract: Although power allocation considerably affects the symbol error rate (SER) performance of a two-path successive relay system (TPSRS), it is not yet studied in a full interference cancellation (FIC) scenario. In this paper, we develop a suboptimal power allocation scheme for the TPSRS-FIC through minimizing an SER-based cost function. To obtain a closed-form power allocation solution, the cost function is defined as a part of the Taylor series expansion of the theoretical SER. Simulation results show that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Recent works in [16], [17] considered the IRI cancellation proposed in [14] in the two-path relay scheme and tried to further improve the performance by adopting power allocation or relay selection. Chu et al [16] proposed a power allocation method in order to minimize the symbol error rate with partial channel state information (CSI) at the source.…”
Section: A Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent works in [16], [17] considered the IRI cancellation proposed in [14] in the two-path relay scheme and tried to further improve the performance by adopting power allocation or relay selection. Chu et al [16] proposed a power allocation method in order to minimize the symbol error rate with partial channel state information (CSI) at the source.…”
Section: A Related Workmentioning
confidence: 99%
“…Chu et al [16] proposed a power allocation method in order to minimize the symbol error rate with partial channel state information (CSI) at the source. In [16], the authors assumed that the source uses the same transmit power to both the relays, and both the relays transmit with the same power to the destination. However, this approach may not be optimal in a typical/practical environment where the channel power gains of different links are often different.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…, together withx (n) r stored at TS n, another XOR operation is performed through (13). In order to recover x (n) i , g(1, 1) = g(−1, −1) = −1 and g(1, −1) = g(1, −1) = 1 are supposed to be satisfied.…”
Section: A Bpsk Modulationmentioning
confidence: 99%
“…The orthogonality of the real part and the imaginary part of the symbol was utilized to distinguish the information and interference in [12]. More research on two-path relay in recent years can be found in [13] [14].…”
Section: Introductionmentioning
confidence: 99%